Kekosongan yang Penuh: Sebuah Tafsiran atas Kosmologi Sunda - Djunatan, Stephanus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2013)
Cosmology is not limited to the questions of the origin and the end of all beings or to the law and order of the universe from the perspective of modern sciences. One can perceive cosmology as a knowledge model of the universe which sets in a non-Western model of knowing. The Sundanese cosmology is an example of this model. Instead of mathematical and physical explanation, it focuses on the mythological description of the universe. Such description can be found in narrative poems (pantun) and pious lessons. This paper observes the non-western knowledge model and puts it in its context, which is geographically equivalent to Southern and Eastern Asia. An overview of the Rig Veda and Daodejing is included to describe the cosmological models in these cultural contexts. The Sundanese cosmology reverberates these models. An elaboration of Sundanese narrative poems and an old Sundanese manuscript, Sewaka Darma, indicates the similarities of the Sundanese cosmology to the cultural contexts and the knowledge models referred to. The Sundanese model enacts ‘mountain’ and the metaphor of ‘filled nothingness’ as the cosmological model. The Sundanese cosmological model portrays a down-upward journey to experience ‘moksa’ (the ultimate enlightment). This journey utilizes meditative practices and everyday deeds by means of our social and cultural roles.